2016
DOI: 10.1016/j.ijsu.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Acute appendicitis in an overweight and obese Mexican population: A retrospective cohort study

Abstract: The outcomes in the Mexican adult obese population with acute appendicitis when a laparoscopic appendectomy is performed are as good as reported in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Literature reports that laparoscopic appendectomy is associated with a higher complication rate and high cost as compared to the conventional open procedure 13 . Although laparoscopic appendectomy has the advantages of optimal abdominal cavity exploration, less hospital stay and less post-operative pain which is in line with our study 3 . The difference of the technique in both methods may transform the consequences in term of complication and costs 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Literature reports that laparoscopic appendectomy is associated with a higher complication rate and high cost as compared to the conventional open procedure 13 . Although laparoscopic appendectomy has the advantages of optimal abdominal cavity exploration, less hospital stay and less post-operative pain which is in line with our study 3 . The difference of the technique in both methods may transform the consequences in term of complication and costs 14 .…”
Section: Discussionsupporting
confidence: 90%
“…Appendectomy has been proven to the standard care for the treatment of acute appendicitis since its introduction in 1894 by McBurney 2 . Literature already proves that laparoscopic surgery has many advantages like fast recovery, less pain at the site of surgery and shorter hospital stay 3 . In complicated appendicitis, laparoscopic appendectomy has major advantages like decreased risk of wound infection & complete vision of peritoneal cavity 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Acute appendicitis is the most common indication for an emergency abdominal surgery in the world, with a lifetime incidence of around 10% [1] , [2] . The etiology of acute appendicitis is secondary to appendiceal obstruction, the commonest causes of this obstruction are lymphoid hyperplasia and, fecal stasis with fecaliths [3] , [4] , [5] ; other rare causes have been described such as carcinoid tumor of the appendix, pinworm, eosinophilic appendicitis, granulomas, and actinomycosis among others [3] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that laparoscopic appendectomy is associated with a higher complication rate and higher charges regardless the conventional procedure (33), although the advantages of the laparoscopic approach (optimal abdominal cavity exploration, fast recovery) are emphasized elsewhere (6). The different techniques proposed in literature for both approaches can obviously change the results in terms of patient's comfort, complications and costs (2, [4][5][6][7][8]. The open technique we proposed is commonly adopted in many cases (34,35), as well as the three-port laparoscopic procedure, used for appendectomy and other abdominal procedures (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional, laparotomic approach is still accepted, as reported in some studies based on surgical expertise (4). Many studies suggest that the laparoscopic approach for performing appendectomy (LA) has many advantages like faster recovery, less postoperative complications, better cosmetic impact, less postoperative pain and shorter hospital stay (5,6). At first these advantages had been demonstrated in uncomplicated appendicitis (7).…”
Section: Introductionmentioning
confidence: 99%